Biochemical and molecular approaches to understanding protein import into peroxisomes. (August 2000) - Baker, A.; Charlton, W.; Johnson, B.; Lopez-Huertas, E.; Oh, J.; Sparkes, I.; Thomas, J.
Abstract : Peroxisomes are eukaryotic organelles that perform diverse and variable functions. Although genetic studies in yeasts and mammals have identified approximately 20 genes (PEX genes) required for the biogenesis of this important organelle, biochemical studies of protein targeting and import have lagged behind and in many cases we have no idea of the function of the PEX gene products (peroxins). Using an import assay in vitro derived from sunflower cotyledon cells and recombinant proteins, we have obtained translocation intermediates on the peroxisome import pathway and are using cross-linking to identify interacting partners. We have also used antibodies raised against human PEX14 to inhibit the import of matrix proteins in this system. To obtain homologous antibodies for inhibition experiments, to immunoprecipitate cross-linked products and to enable us to study the import pathways of peroxins we have cloned and characterized plant orthologues of three PEX genes, PEX6, PEX10 and PEX14.